Brief Report: Changes in Levels of Inflammation After Antiretroviral Treatment During Early HIV Infection in AIDS Clinical Trials Group Study A5217. (1st May 2017) - Macatangay, Bernard J.; Yang, Ming; Sun, Xin; Morton, Jessica; De Gruttola, Victor; Little, Susan; Hogan, Christine; Rinaldo, Charles R.
Abstract : Background: We evaluated the changes in the levels of soluble biomarkers of inflammation and coagulation and T-cell activation among participants of AIDS Clinical Trials Group Study A5217 who were started on antiretroviral therapy (ART) within the first 6 months of HIV infection. Methods: Cryopreserved specimens were obtained pre-ART (week 0), at the time of virologic suppression (week 36), and at 36 weeks after treatment interruption (week 72). Levels of D-dimer, C-reactive protein (CRP), and soluble CD14 (sCD14) were measured in plasma, whereas T-cell activation levels, defined as the frequencies of CD4 + and CD8 + T cells coexpressing HLA-DR and CD38, were measured in peripheral blood mononuclear cells. Results: D-dimer levels were significantly lower at viral suppression ( P = 0.031), whereas CRP and sCD14 levels remained similar to pre-ART levels. At viral suppression, levels of the soluble markers did not correlate with each other. CD4 + T-cell counts pre-ART tended to modestly correlate with levels of D-dimer ( r = 0.35; P = 0.058) and CRP ( r = 0.33; P = 0.078). At 36 weeks after treatment interruption (week 72), D-dimer levels returned back to pre-ART levels. However, CD8 + T-cell activation was significantly lower than pre-ART levels (35.8% at week 0 vs 28.9% at week 72; P = 0.004). Conclusions: Among the A5217 participants who started ART within the first 6 months of HIV infection, high levels of sCD14 and CRP remain similar to pre-ART levels, suggesting that immune damage occurring in the initial stages of infection persists despite short-term virologic suppression. Abstract : Supplemental Digital Content is Available in the Text.